Genome-wide identification and expression analysis of the GRAS transcription in eggplant (Solanum melongena L.) - Yang, Ting; Li, Cheng; Zhang, Hui; Wang, Jingyu; Xie, Xiaofang; Wen, Yongxian (Frontiers in Genetics, 2022)
GRAS proteins are plant-specific transcription factors and play important roles in plant growth, development, and stress responses. In this study, a total of 48 GRAS genes in the eggplant (S. melongena) genome were identified. These genes were distributed on 11 chromosomes unevenly, with amino acid lengths ranging from 417 to 841 aa. A total of 48 GRAS proteins were divided into 13 subgroups based on the maximum likelihood (ML) model. The gene structure showed that 60.42% (29/48) of SmGRASs did not contain any introns. Nine pairs of SmGRAS appeared to have a collinear relationship, and all of them belonged to segmental duplication. Four types of cis-acting elements, namely, light response, growth and development, hormone response, and stress response, were identified by a cis-acting element predictive analysis. The expression pattern analysis based on the RNA-seq data of eggplant indicated that SmGRASs were expressed differently in various tissues and responded specifically to cold stress. In addition, five out of ten selected SmGRASs (SmGRAS2/28/32/41/44) were upregulated under cold stress. These results provided a theoretical basis for further functional study of GRAS genes in eggplant.